A comment to Gobo: the next challenge – from mixed to merged methods. Issue 3 (12th September 2016) - Hervieux, Chantal
Abstract : Purpose: The purpose of this paper is to further the discussion on points made by Giampietro Gobo, provide additional information on the place of qualitative research in management, and question the space of merged methods. Design/methodology/approach: Use a conversational approach as well as a review of qualitative vs quantitative research in three top tier journals for the years 2013-2016 (by a simple count). Findings: Quantitative methods remain very much mainstream in management research, yet one finds that for one of the journals, space is evenly shared between qualitative and quantitative methods. Research limitations/implications: This is a viewpoint and does not offer a systematic review of all top tier management journals. Originality/value: It is hope that with this viewpoint debate as to the space of qualitative research, and merged methods can be stimulated.